Higher Serum Level of MMP-3 and Homocysteine in Patients Admitted With COVID-19: Tingkat Serum MMP-3 dan Homosistein yang Lebih Tinggi pada Pasien yang Dirawat dengan COVID-19 - Nasrin Hayawi; Masoud Youssefi; Mohammad Soukhtanloo; Lida Jarahi; Elham Pishbin; Farnaz Zahedi Avval (Academia Open, 2024)
Background: SARS-CoV-2 predominantly affects the lungs, leading to severe acute respiratory syndrome (ARDS). The lack of specific biomarkers underscores the urgent need for novel indicators for early diagnosis and severity assessment of COVID-19. Specific Background: Matrix metalloproteinase-3 (MMP-3) is implicated in various inflammatory diseases, particularly viral infections, while homocysteine (Hcy) plays a crucial role in maintaining cell homeostasis and regulating inflammatory responses. Knowledge Gap: Despite their relevance in inflammation, the potential of MMP-3 and Hcy as biomarkers for COVID-19 remains underexplored. Aims: This study aimed to evaluate the serum levels of MMP-3 and Hcy in COVID-19 patients and assess their utility in diagnosis and severity prediction. Results: A study analyzing 90 serum samples from 60 ICU patients and 30 healthy controls found elevated CRP levels, higher Hcy and MMP-3 levels in the moderate group, but lower in the ICU group, with a significant correlation between MMP-3 activity and Hcy levels. Novelty: This research highlights the potential role of MMP-3 and Hcy as valuable biomarkers for COVID-19 diagnosis. Implications: While MMP-3 and homocysteine may aid in the diagnostic process, they could not be reliably used to predict severity outcomes in COVID-19 patients. Further studies are warranted to clarify the clinical implications of these biomarkers in the context of COVID-19. Highlights: MMP-3 and homocysteine identified as potential COVID-19 biomarkers. No correlation found between biomarkers and disease severity. Further research needed for clinical utility assessment. Keywords: COVID-19, MMP-3, homocysteine, biomarkers, diagnosis